Bubble-Wrapped: An Unusual Developmental Cataract - Akanksha Sharma; Parul Chawla Gupta; Ranjan Kumar Behera (QJM: An International Journal of Medicine, 2026)
Abstract An 11-year-old girl presented with progressive visual diminution in the right eye, with previous left cataract surgery. Slit-lamp examination revealed multiple discrete, circular lenticular opacities with central dark zones and dense white peripheral halos, producing a distinctive “bubble-wrap” appearance. The lesions were predominantly nuclear and varied in size. Although bubble-like cataract morphologies have been described following ocular trauma and in retinitis pigmentosa, this appearance has not, to our knowledge, been reported in a developmental cataract. This may represent a novel morphological variant, expanding the phenotypic spectrum of pediatric cataracts.